A Book Review of "Max Weber and the Theory of Modern Politics" - Mohammad Hossein Jamshidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
We briefly reviewed and criticized David Beetham’s book of “Max Weber and the Theory of Modern Politics”. This work produces the most comprehensive framework about Max Weber’s political theory with and analytical method and a historical perspective. It studies the review of the central concern of Weber to prospects for the liberal parliament in the authoritarian societies in the era of mass politics and bureaucratic organizations. It shows how this concern has led him to review the theory of democracy.The special feature of this book is the full dominance of the writer about the widespread German works in Weber’s political thought of. This book is an authoritative guide about Max Weber’s political philosophy. Although it relatively has a logical structure, it is rather understandable and it is away from complexity, grandiloquence, literary gravity and ambiguity. Moderation approach governs it. This book needs to be reviewed and criticized like any other scientific works. So, we have reviewed this book, based on the rational and methodical criteria, and we have tried to express as far as possible its advantages and disadvantages without prejudice and ignorance.